2017
DOI: 10.1128/aem.00538-17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tetracycline Dose and Treatment Mode on Selection of Resistant Coliform Bacteria in Nursery Pigs

Abstract: This study describes the results of a randomized clinical trial investigating the effect of oxytetracycline treatment dose and mode of administration on the selection of antibiotic-resistant coliform bacteria in fecal samples from nursery pigs. Nursery pigs (pigs of 4 to 7 weeks of age) in five pig herds were treated with oxytetracycline for Lawsonia intracellularis-induced diarrhea. Each group was randomly allocated to one of five treatment groups: oral flock treatment with a (i) high (20 mg/kg of body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…Epidemiological studies revealed either an increase in antimicrobial resistance in populations treated more often with antibiotics [6,7], or a beneficial effect on resistance levels after the introduction of national antimicrobial usage (AMU) reduction campaigns [8]. Under defined experimental conditions, the effect of a selective pressure by antimicrobial usage on the frequency of phenotypically resistant bacteria in swine [9] or the total resistome of bacterial populations [10] was proven. In general, under field conditions, in livestock, the association between AMU and AMR is difficult to assess because additional factors such as vaccination, feed supplements, hygiene conditions and management characteristics also have an impact [11].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies revealed either an increase in antimicrobial resistance in populations treated more often with antibiotics [6,7], or a beneficial effect on resistance levels after the introduction of national antimicrobial usage (AMU) reduction campaigns [8]. Under defined experimental conditions, the effect of a selective pressure by antimicrobial usage on the frequency of phenotypically resistant bacteria in swine [9] or the total resistome of bacterial populations [10] was proven. In general, under field conditions, in livestock, the association between AMU and AMR is difficult to assess because additional factors such as vaccination, feed supplements, hygiene conditions and management characteristics also have an impact [11].…”
Section: Introductionmentioning
confidence: 99%
“…Enumeration of dark red colonies with a size of >0Á5 mm was performed after 24 h of incubation at 37°C and proportions (%) of R strains were estimated. In a previous study, 100 such colonies were all confirmed to be E. coli (Graesboll et al 2017). Such a control was not carried out in the current work, and we will use the term coliforms, although they are likely to be E. coli.…”
Section: Experimental Set Up and Amr Testingmentioning
confidence: 89%
“…5 g each. To determine pretreatment levels (T0) of R coliforms, samples were 10-fold diluted in DPBS, and 20 µl of each dilution were spotted in duplicate for CFU determination on McConkey agar (Oxoid, Roskilde, Denmark) plates with and without antimicrobials as described (Graesboll et al 2017;. Antimicrobials (Sigma) were added at concentrations corresponding to 29breakpoint concentration and 49breakpoint concentration (29 BPC and 49 BPC), respectively, of each specific antimicrobial according to EUCAST criteria (EUCAST 2019): ampicillin (Amp) at 16 and 32 lg ml À1 , cephalexin (Cpn) at 32 and 64 lg ml À1 , ceftiofur (Cef) at 2 and 4 lg ml À1 , and tetracycline (Tet) at 16 and 32 lg ml À1 .…”
Section: Experimental Set Up and Amr Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is worth noting that TCs have been employed also as healing agent for digital dermatitis treatment in dairy cattle [93]. For those reasons, pigs, livestock and poultry are still exposed to a huge range of antimicrobials while the long term effect on the environment, besides antibiotic resistance [94,95], or effects, when consumed by the animal or human species, on the overall individual health status have been partially investigated. As annual production and consumption increase, increasing volumes of antimicrobials will be used each year if nothing is done to reduce their usage with a consequent increase of antimicrobial resistant organisms.…”
Section: Tetracyclines In Veterinary Practicementioning
confidence: 99%